VET in the European aircraft and space industry - Bremer, Rainer [Verfasser] (My University, 2008)
"This article aims to take up a mirror image-oriented position of the EQF and the announced ECVET system. It seeks to be concerned with the effects that the EQF transformation process into the respective NQF might have on the underlying systems of vocational education and training. A comparison is drawn between the competence development the four different VET systems in France, Germany, Spain, and the UK initiated by the identical qualification demands of the sector of aircraft industry (AIRBUS plants in France, Germany, Spain, and the UK). This serves as a finding for the evaluation of the EQF and the effects it will could on the sector of the European aircraft industry. Three hypothesises on: convergence of skill requirements because of the technologies and procedures tend to become the same all over the world if the same products are manufactured; divergence of the national VET systems as a consequence of adaptation such requirements; and a structural reference between requirements and the development of competence, are tested and validated." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.4.1.4 Verarbeitendes Gewerbe; G 1.2.3.2 Anforderungen & Bedarfe; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsbildung; Kompetenzentwicklung; Qualifikationsanforderung; Europäischer Qualifikationsrahmen; Flugzeugindustrie; Luft- und Raumfahrtindustrie; Fallbeispiel; Bundesrepublik Deutschland; Frankreich; Spanien; Großbritannien